Global warming and soybean yield: understanding the effects of climate change: GLOBAL WARMING AND SOYBEAN YIELD: UNDERSTANDING THE EFFECTS OF CLIMATE CHANGE - JYOTI SANKHALA; R T SHENDE; RISHIRAJ RAGHUVANSHI; ASTHA PARDESHI; ARUN WAKTALIYA; GANESH MASKE (Journal of Oilseeds Research, 2025)
Soybean is a crucial crop for global food security, providing essential nutrients for human consumption, animal feed and biofuel production. However, the challenges posed by climate change threaten the stability and sustainability of soybean production. Rising global temperatures, projected to increase by 2.0 to 6.4 °C, along with a predicted 59 cm rise in sea levels by the end of the 21st century, are contributing to more frequent heat waves, droughts, floods, and unpredictable precipitation patterns. These changes are having a profound impact on agricultural systems, with significant repercussions for crop yields and food security worldwide. In particular, climate change is exacerbating the vulnerabilities of soybean farming. Increasing temperatures and shifting rainfall patterns, along with the increased frequency of extreme weather events, are disrupting the growth and productivity of soybean crop. Additionally, the rising pressure from pests and diseases, which thrive in warmer conditions, further compromises soybean yield and quality. This review explores recent research on the direct and indirect impacts of climate change on soybean production, the physiological responses of the crop to these stressors, and the mitigation strategies being developed to address these challenges. A deeper understanding of these factors is critical for adapting soybean farming practices to ensure resilience, enhance productivity, and safeguard food security in the face of a changing climate.